Heart failure risk assessment in patients with hypertrophic cardiomyopathy based on the H2FPEF score - Laenens, Dorien; Zegkos, Thomas; Kamperidis, Vasileios; Wong, Raymond C. C.; Li, Tony Yi-Wei; Sia, Ching-Hui; Kong, William K. F.; Efthimiadis, Georgios; Poh, Kian Keong; Ziakas, Antonios; Bax, Jeroen J.; Ajmone Marsan, Nina (John Wiley & Sons, 2025)
Aims
The aim of this study was to investigate whether the H2FPEF score, which was developed to improve the diagnosis of heart failure (HF) with preserved ejection fraction, is associated with HF outcomes in patients with hypertrophic cardiomyopathy (HCM).
Methods and results
Patients with HCM and preserved left ventricular ejection fraction (LVEF ≥50%) were included from a multicentre registry and the H2FPEF score was calculated. Patients were divided into three groups: low (0-1), intermediate (2-5) and high (6-9) H2FPEF score. The primary combined endpoint was a composite of all-cause death and HF admissions, while the secondary endpoints were all-cause death and HF admissions separately. A total of 955 patients were included (age 51 ± 17 years, 310 [32.5%] female). Patients with a high H2FPEF score (n = 105) were more often female, and presented with more symptoms and comorbidities. On echocardiography, patients with a high H2FPEF score had lower LVEF, more impaired diastolic function and more frequently left ventricular outflow tract obstruction. During follow-up (median 90 months [interquartile range 49-176]), 103 (11%) patients died and 57 (6%) patients had a first HF hospitalization. Event-free survival rate for the primary combined and secondary endpoints was lower for patients with an intermediate and high H2FPEF score. On multivariate Cox regression analysis, female sex (hazard ratio [HR] 1.670, 95% confidence interval [CI] 1.157-2.410; p = 0.006), Asian ethnicity (HR 6.711, 95% CI 4.076-11.048; p < 0.001), ischaemic heart disease (HR 1.732, 95% CI 1.133-2.650; p =  0.011), left atrial diameter (HR 1.028, 95% CI 1.005-1.051; p = 0.016) and intermediate (HR 2.757, 95% CI 1.612-4.713; p < 0.001) or high H2FPEF score (HR 3.689, 95% CI 1.908-7.134; p < 0.001) were independently associated with the primary combined endpoint.
Conclusion
The H2FPEF score is independently associated with HF outcome in patients with HCM and may be considered for risk stratification.